DESAIN BUKU CERITA ANAK BERLATAR KEGIATAN KEPRAMUKAAN PENGGALANG - Sifa Fauziah; Wagiran Wagiran (STKIP Siliwangi, 2017)
Children’s low interest in reading storybook is caused by the lack of variety of books in the markets. One of the effort to increase the variety of books is to use the settings of a Scout’s Raiser activity. The aim of this study is to find out the quality of the books in the markets, the needs of storybooks based on the Scout’s Raiser activity, and to design a storybook based on the setting of Scout’s Raiser Activity. The data was collected through observation, interview, and questionnaires. The result of the study was a children’s storybook with a Scout’s Raiser activity as the background of the story. The students want a storybook about adventure, which is using a communicative language, contains an illustration that describes the story, and also a cheerful color that can attract them. The design of the storybook based on the settings of Scout’s Raiser activity was arranged based on the questionnaires.